Clear cell carcinoma arising from scar endometriosis: A case report and literature review - Chun-Jui Wei; Shu-Han Huang (Tzu Chi Medical Journal)
Scar endometriosis is uncommon and defined as the presence of ectopic endometrial glands in abdominal soft tissues after a gynecological operation. Malignant transformation has been reported but remains rare. Carcinogenesis occurs in ectopic endometrial tissue with repeated hormone stimulation during the menstrual cycle. We present a case of clear cell carcinoma directly arising from scar endometriosis after a cesarean section and review all 16 cases reported.